2017
DOI: 10.17352/2455-8400.000031
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity of Mercury Chloride (Hgcl2) and Cadmium Chloride (Cdcl2) on the behavior of freshwater fish, Percocypris Pingi

Abstract: The present study was performed to examine acute toxicity of two water-borne metals (Hg and Cd) by static bioassays. Fingerlings Percocypris pingi (P. pingi) were exposed to a range of concentrations of heavy metals and the mortality rate were investigated after 24, 48, 72 and 96h. The median lethal concentration (LC 50) was determined with Probit analysis. The LC 50 values of mercury chloride for the P. pingi at 24, 48, 72 and 96h were 0.441, 0.347, 0.327 and 0.327 mg/L, respectively. But the LC 50 values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…The LC 50 96 h values of mercury chloride for the Percocypris pingi was 0.327 mg/L. But the LC 50 96 h value of cadmium chloride was 0.081 mg/L [17]. And in this study, the LC 50 96 h values of zinc for the Percocypris pingi was 2.852 mg/L.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…The LC 50 96 h values of mercury chloride for the Percocypris pingi was 0.327 mg/L. But the LC 50 96 h value of cadmium chloride was 0.081 mg/L [17]. And in this study, the LC 50 96 h values of zinc for the Percocypris pingi was 2.852 mg/L.…”
Section: Discussioncontrasting
confidence: 52%
“…Other studies reported that the heavy metals have a complex effect on the aquatic environment and this effect relies on the physicochemical characteristics of water and fish species [35,36]. And metal toxicity may be modified by physicochemical parameters for Percocypris pingi [17]. So we detected the physicochemical characteristics (e.g.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation